(untitled) (Eurasian Research Bulletin, 2022)
This article deals with the heroes of the novel “Between Two Doors”, one of the most popular works of modern Uzbek literature. There is a comprehensive analysis of the female image . A special place in the work of Utkir Khashimov is occupied by the novel “Between Two Doors”. The writer is concerned not only with the pressing social issues of today, but with eternal moral problems. In particular, by calling “Between Two Doors”, the writer means the path of person, which he walked from birth to death.